Rates of Presurgical Underestimation of Breast Cancer after Standardized Assessment of Breast Calcifications - Timpe, L.; Berkemeyer, S.; Puesken, M.; Tio, J.; Heindel, W.; Weigel, S. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: To determine the frequency of histopathological underestimation of breast cancer after vacuum-assisted biopsy (VAB) in standardized assessment of breast calcifications compared to postsurgical diagnosis.Materials and Methods: The retrospective study included acquired data of 506 consecutively examined women, who underwent VAB for the assessment of pure calcifications after standardized digital mammographic and sonographic imaging. 119/506 (24.5 %) women underwent further surgical procedures: 37 women had a surgical diagnostic excision biopsy, 82 women a surgical procedure based on a therapeutic concept. Presurgical results of VAB were compared with the postsurgical histopathological reports.Results: In 91/119 women (76.5 %) the final histology was malignant. The rate of ductal carcinoma in situ (DCIS) was 79.1 % (72/91) and the rate of invasive carcinoma was 20.9 % (19/91). In 9/37 women with diagnostic excision biopsy, the presurgical status of benign or uncertain changed to a postsurgical diagnosis of malignant (24.3 %). In eight cases underestimation included DCIS (21.6 %) and in one case invasive cancer (2.7 %). Seven of the nine underestimated cases (77.8 %) resulted from excision biopsy of atypical epithelial proliferation of ductal type (AEPDT, positive predictive value 30.4 % (7/23)). After surgery due to DCIS in 7/71 women invasive breast cancer was diagnosed (9.9 %). In 11/82 women with oncological surgery, invasive cancer was already diagnosed by VAB.Conclusion: Underestimation of invasive cancer in terms of presurgical DCIS diagnosis can be minimized by the standardized assessment protocol to about 10 %. Underestimation of DCIS is mainly related to presurgical diagnosis of AEPDT.Key Points:• The standardized use of digital mammographic and sonographic imaging prior to vacuum-assisted biopsy is suitable for minimizing underestimation of invasive breast cancer. AEPDT represents a high risk diagnosis for underestimation of DCIS.Citation Format:• Timpe L., Berkemeyer S., Puesken M. et al. Rates of Presurgical Underestimation of Breast Cancer after Standardized Assessment of Breast Calcifications. Fortschr Röntgenstr 2015; 187: 445 – 449
Keywords: breast; breast cancer; biopsy breast; ultrasound; vacuum-assisted biopsy; quality assurance